The instruction process of lawsuits solved through arbitration in the Kingdom of Valencia: Els Ports and El Maestrat regions (13th-14th centuries) - Royo Pérez, Vicente (Cuadernos de Historia del Derecho, 2021)
In this article, we analyse the instruction process of lawsuits solved through arbitration. After signing the agreement, the mediators, who have been appointed by the parties, begin to investigate what led them to reach a sentence, the ruling that settles the arbitration. Despite the relevance of this procedure in the development of the arbitration, the Fueros de Valencia did not regulate either the tasks performed by mediators or the time spent to accomplish such tasks. Likewise, it was not customary to leave a written account of the arbitrators’ actions from the moment of signing the agreement to issuing the sentence. However, it is possible to know the mediators’ responsibilities thanks to the information enclosed in these two documents –agreement and sentence–, which shows the existence of three different phases. Therefore our aim is to analyse these three phases, investigation, examination and resolution of the conflicts solved through arbitration. Thus, our attention will focus in the sources produced by members of different social classes in the Els Ports and El Maestrat regions during the 13th and 14th Centuries.
Keywords: Law; arbitration; conflicts; conflicts resolution; Kingdom of Valencia; Middle Ages